Glycosylation of immune system proteins and its role in autoimmune diseases and cancer - Trzyna, Anna; Tabarkiewicz, Jacek; Mazur, Artur (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Structural glycans have great biological significance and are involved in signaling and cell communication of the immune system. They are attached to proteins and lipids in an enzymatic process called glycosylation where glycosyltransferase and glycosidases bind sugar residues and lead to the formation of bioconjugates. Aim. In this paper we describe the importance of glycosylation in the immune system and its changes in diseases. Material and methods. This review was performed according to systematic literature search of major bibliographic databases. Results. Proper glycosylation ensures the functioning of the organism, however, defects in structural glycans of immune system changes their properties and can lead to disorders and further to autoimmune diseases. It has been also proven that glycosylation of autoimmune system is changed during cancer. In this paper we described types of structural glycans, significance of glycosylation of selected components of the immune system and its modifications in disorders. Conclusions. Knowledge about changes in the glycosylation in diseases is the key to understanding the processes of autoimmune diseases and may allow the development of new treatments in the future.
Keywords: Glycosylation; Immunity; Cellular; Humoral; Autoimmune Diseases